(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
Many behavior therapists have written about the therapeutic relationship with consent about its importance but not about its role in therapy: for some, it is seen as a determinant variable or factor and for others, as the main mechanism of change. The literature of therapeutic relationship evaluation demonstrates that it is a predictive variable of therapeutic results regardless of the theoretical approach. Some evaluation instruments were gathered and the Working Alliance Inventory (WAI) is presented along with some ways to use it. Also discussed is the importance of the research at the behavior therapy field relating standardized instruments results with behavioral categories.